Promotion of Safety and Health at Work: The Venezuelan case - Andara Peña, Bernavé (Gaceta Laboral, 2024)
The objective of this article is to identify the aspects of promoting safety and health in the workplace upon regarding the new appearance of the matter as a fundamental right, in accordance with the resolution at the 110th International Labor Conference of the ILO dated June 10, 2022, whose decision obliges the Member States to commit to, respect and promote a safe and healthy work environment, whether or not they have ratified the corresponding Conventions, and the Venezuelan reference; along with the bases that support such regulation, based on international standards on the matter. The type of research is applied, documentary and descriptive, with bibliographic documentary design, under the technique of documentary analysis. In this order of ideas, the problem of safety and health at work requires the implementation and implementation of coherent policies, with a collective approach, of an interdisciplinary nature, which manages to delimit, given the complexity of the subject, the risks within the area. , proceeding to its eradication and fulfilling a vital mission that is none other than to inform workers and employers under strict training, regarding the prevention of risks within the labor area, both in times of crisis and in the face of future emergencies. and challenges, projecting itself in support of business survival and continuity as a preponderant factor in economic reactivation and recovery after times of COVID-19 and unexpected global political changes.